Experimental and molding study of the vaporization process of newly developed and well-established jet fuel surrogates. (December 2022) - Al Zaitone, Belal; Alsulami, Radi A.; Mohammad, Akram
Abstract: Real jet fuels have hundreds of individual hydrocarbon species with varying physical and chemical properties. Surrogate fuels containing mixtures of a small number of components have been developed to emulate the behaviors of the parent fuels. Often surrogates are derived solely based on the gas-phase combustion behavior and thus are not constrained to match physical phenomena, such as atomization and vaporization. Thus, these fuels can subsequently exhibit different behaviors than the parent fuel they are designed to emulate, especially when introduced in a two-phase system. This work explores the ability of selected established and newly developed/proposed surrogate jet fuels to mimic the properties necessary for the two-phase conversion process, including the vaporization behavior of real fuel spray. The droplet lifetime/vaporization dynamics is measured using a single droplet levitating device (acoustic levitator). The newly developed surrogates show a satisfying emulation of the parent jet fuel's physical and chemical properties, including SMD, CN, LHV, MW, and vaporization evolution. Most notably, the binary solution consisting of n-dodecane and toluene predicted the physical and chemical properties of the parent fuel closely, with a total maximum deviation from the selected targeted fuel properties ∼12.6% compared to ∼52% of the well-established previously developed Dooley 1st surrogate.